Exploring the effect of stakeholder relationship quality on technological innovation in off-site construction: the mediating role of the knowledge sharing - Ma, Shengbin; Li, Zhongfu; Li, Long; Yuan, Mengqi; Yin, Xianfei (Journal of Civil Engineering and Management, 2023)
Off-site construction (OSC) is generally propagated as a sustainable and green construction method in the global construction industry. Over the past few decades, OSC has become famous worldwide for its numerous benefits. Technological innovation can speed up the development of OSC and has attracted a lot of attention from stakeholders who are promoting technological innovation by seeking collaborations. OSC is different from traditional manufacturing, and little effort has been spent on how the stakeholder relationship quality affects technological innovation. This study therefore makes efforts to explore the mechanism of how stakeholder relationship quality influences the OSC technological innovation and to explain the stakeholder relationship quality in terms of communication, trust, and commitment. This paper constructs a multidimensional hypothesis model consisting of five concepts: communication, trust, commitment, knowledge sharing, and technological innovation. A valid sample of 125 was collected through a questionnaire survey in mainland China. The sample data were dealt with and analyzed using partial least squares structural equation modeling (PLSSEM) to validate the proposed hypothesis model. The results reveal that trust and knowledge sharing affect technological innovation directly. Communication and commitment are not identified to have statistically significant influences on technological innovation in OSC. Communication, trust, and commitment positively contribute to knowledge sharing. Last, knowledge sharing completely and partially mediates between relationship quality and technological innovation. This study explores the impact of stakeholder relationship quality on OSC technological innovation and verifies the mediating role of knowledge sharing. These findings provide valuable theoretical guidance for OSC technological innovation and practical insights for stakeholders to promote technological innovation by enhancing relationship quality and knowledge sharing.First published online 13 December 2022